Role of Labelling on Sustainable Consumption of Fresh Fruit and Vegetables - Pashova, Sabka; Radev, Radoslav (Research Papers, 2022)
The purpose of this study is to present the mandatory and voluntary details in the labelling of fresh fruits and vegetables, and on the basis of the analysis to establish their role in sustainable consumption. The study presents the Bulgarian and Union legislation in the field of marking of fresh fruits and vegetables. The conducted research provides an opportunity for studies on the completeness of the legislative framework, as well as the specifics of the details of the labelling of fresh fruits and vegetables. Interrelation between the regulated requirements and the sustainable consumption of fresh fruits and vegetables has been established.
Keywords: Sustainable consumption; Labelling; Fresh fruits and vegetables